2016
DOI: 10.1002/slct.201500017
|View full text |Cite
|
Sign up to set email alerts
|

Rule of Hydrophobicity/Hydrophilicity Balance in Membrane‐Disrupting Antimicrobial Activity of Polyalkylamino Cyclodextrins Synthesized via Click Chemistry

Abstract: Emergence of drug‐resistant bacterial pathogens and the concurrent demand for new antibiotics has led to membrane‐active antimicrobial cyclodextrin (CD) development. CDs contain polyalkylamino groups; molecule polyfunctionalization was achieved via a click reaction. A survey using CDs with systematically varied functionalities clarified the unique correlation of their antimicrobial activity with the molecules’ hydrophobicity/hydrophilicity balance. The optimum hydrophobicity of the membrane‐active molecule was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…To examine the effect of the molecular scaffold, a pentylamino group was introduced into glucose, maltose, maltooctaose, and amyloses as the antimicrobial group on the γ‐CD disrupted bacterial membrane . To attach the pentylamino groups onto each sugar, a microwave (MW)‐assisted Huisgen 1,3‐dipolar cycloaddition reaction known as the click chemistry reaction was adopted, which enabled polyfunctionalization of the CD molecule . The maltooctaose derivative 3 was synthesized as shown in Scheme a.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the effect of the molecular scaffold, a pentylamino group was introduced into glucose, maltose, maltooctaose, and amyloses as the antimicrobial group on the γ‐CD disrupted bacterial membrane . To attach the pentylamino groups onto each sugar, a microwave (MW)‐assisted Huisgen 1,3‐dipolar cycloaddition reaction known as the click chemistry reaction was adopted, which enabled polyfunctionalization of the CD molecule . The maltooctaose derivative 3 was synthesized as shown in Scheme a.…”
Section: Methodsmentioning
confidence: 99%
“…17) Correlation of the hemolysis of rabbit red blood cell by CDs with log P values of the corresponding substituted glucose of CDs 8-21 is shown in Fig. 4.…”
Section: Application Of the Mw-assisted Click Reaction To The Synthesmentioning
confidence: 99%
“…16,17) In the case of natural antibacterial peptides, the positively charged amino groups interact with negatively charged bacterial cell membranes, and their hydrophobic groups interact with polar lipid acyl chains in the membrane, which leads to bacterial membrane disruption and the inhibition of bacterial proliferation. Therefore, the introduction of both poly-amino moieties and poly-hydrophobic moieties onto the CD molecule is necessary for its antibacterial action.…”
Section: Application Of the Mw-assisted Click Reaction To The Synthesmentioning
confidence: 99%
“…66 A recent study has correlated antimicrobial activity with the CD molecules' hydrophobicity/hydrophilicity balance. 67 These authors surveyed the hydrophobicity (based on partition coe±cient logarithm (log P)) and antimicrobial activity (based on MIC values) of a series of polyalkyamino CDs. A relatively hydrophilic CD (log P < À0:1) may interact with the bacterial cell membrane's anionic surface, while a relatively hydrophobic CD (log P > 0:1) may disturb the surface interaction, as a result only balanced derivatives can disrupt the bacterial membrane.…”
Section: Mechanism Of Antimicrobial Actionmentioning
confidence: 99%
“…A study has suggested that the di®erences in the cell membrane and lipid molecules of Gram-positive and Gram-negative bacteria may contribute to the varied antimicrobial activities of CDs. 67 A little more hydrophobicity appeared to be essential for a CD interacting with the Gram-negative E. coli membrane, more so than for interacting with the Gram positive B. subtilis membrane. Increasing hydrophobicity may increase antimicrobial activity but is associated with an increase in hemolytic activity.…”
Section: Mechanism Of Antimicrobial Actionmentioning
confidence: 99%